2016
DOI: 10.1007/s11274-016-2123-3
|View full text |Cite
|
Sign up to set email alerts
|

Aurintricarboxylic acid structure modifications lead to reduction of inhibitory properties against virulence factor YopH and higher cytotoxicity

Abstract: Yersinia sp. bacteria owe their viability and pathogenic virulence to the YopH factor, which is a highly active bacterial protein tyrosine phosphatase. Inhibition of YopH phosphatase results in the lack of Yersinia sp. pathogenicity. We have previously described that aurintricarboxylic acid inhibits the activity of YopH at nanomolar concentrations and represents a unique mechanism of YopH inactivation due to a redox process. This work is a continuation of our previous studies. Here we show that modifications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Not only oxidants can induce inhibition of PTPs via oxidation mechanism, but ROS generating compounds such as aurintricarboxylic acid (ATA) can as well. ATA is believed to be a nontoxic compound, and it is still one of the most active inhibitors of the YopH virulence factor from Yersinia bacteria, with IC50 equal to 10 nM (presented in Table 1 ) [ 56 ].…”
Section: Potential Bacterial Ptp Inhibitorsmentioning
confidence: 99%
“…Not only oxidants can induce inhibition of PTPs via oxidation mechanism, but ROS generating compounds such as aurintricarboxylic acid (ATA) can as well. ATA is believed to be a nontoxic compound, and it is still one of the most active inhibitors of the YopH virulence factor from Yersinia bacteria, with IC50 equal to 10 nM (presented in Table 1 ) [ 56 ].…”
Section: Potential Bacterial Ptp Inhibitorsmentioning
confidence: 99%
“…Such correlation was obsevered related to aurintricarboxylic acid (ATA) which reveals high inhibitory effect on PTP1B (47). However, the experiments conducted on other tyrosine phosphatase YopH has shown that the analogs of ATA are weaker inhibitors than their precursor (48).…”
Section: Promising Inhibitors Of Protein Tyrosine Phosphatase Ptp1bmentioning
confidence: 99%